Rural populations have equal surgical and survival outcomes in metastatic colorectal cancer. (October 2014) - Singla, Apresh; Broadbridge, Vy; Mittinty, Murthy; Beeke, Carol; Maddern, Guy J.
Abstract Objective Previous Australian studies have suggested poorer survival of patients with colorectal cancer in remote areas. To date no studies have assessed the geographic disparity in patients with metastatic disease. This retrospective cohort study looks at geographic differences in the surgical care and survival of patients with metastatic colorectal disease. The paper utilises data from the South Australian Clinical Registry for Metastatic Colorectal Cancer (SACRMCC). Design, participants, interventions and main outcome measures Data on patients' socio‐economic status, primary and metastatic tumour characteristics, treatment and survival was extracted from the SACRMCC database. A binomial model analysis was used to identify geographical differences in the surgical treatment of patients and a Cox proportional hazards model was used to identify any geographic differences in survival. Results The findings showed no differences in the diagnosis of liver metastases or provision of liver surgery between geographic areas, however there was a reduced likelihood of liver surgery with increasing age. The median overall survival rate, from the date of diagnosis of metastatic disease, was 20.0 months and the distribution by geographic remoteness was 19.1 months, 20.2 months, 22.0 months and 20.4 months in Major Cities, Inner Regional, Outer Regional and Remote areas respectively. This was not statistically significant. Conclusion Overall, there was no evidence of a geographical disparity in the diagnosis, surgical treatment or survival in metastatic colorectal cancer. This may be due to the shift toward centralising surgical care in South Australia. Nevertheless, there remains a need to improve the uptake of surgical care in the growing elderly population.